Endoscopic resection of early squamous neoplasia of the oesophagus: long-term follow-up in a UK population from a tertiary hospital. Issue 7 (July 2020) - Kuan, Jen Yee; Baskind, Sameul; Kim, Yeson; McGrath, Stephen; Chaparala, Ramakrishna; Assadsangabi, Arash; Prasad, Neeraj; Regi, George; Ang, Yeng
Abstract : Aim: To review the efficacy and outcomes of endoscopic resection in the diagnosis and treatment of oesophageal squamous dysplasia and early neoplasia. Methods: This was a retrospective study between May 2012–2018. Twenty-one patients were treated with or considered for treatment with endoscopic resection at a tertiary hospital in the UK. The primary outcome was curative resection, defined as histologically proven complete resection of the lesion with deep/vertical margin ≥1 mm from neoplasia. Secondary outcomes were changes in staging from endoscopic resection histology, whether there was a complete reversal of dysplasia at 12-months or the latest endoscopic follow-up and 5-year overall survival rate. Results: Seventeen patients (mean age = 66.5 years) with 20 lesions (35% en-bloc; 65% piecemeal resections) had endoscopic resection performed. Complete resection was achieved in 90% of lesions by endoscopic criteria, but this was confirmed in fewer lesions histologically. Curative resection was achieved histologically in 60% of lesions (11 patients) and noncurative resection in 40% of lesions (6 patients). Changes in staging from endoscopic resection histology were found in 79.2% of lesions (41.7% upstaged; 37.5% downstaged). No patients were found to have recurrence at their 12-month endoscopic follow-up. Eight of the 11 patients (72.7%) with curative resection remained clear of dysplasia/neoplasia throughout their follow-up (mean, 24.3 months; median, 19 months). The five-year overall survival rate was 64%. Conclusion: In UK, endoscopic resection is useful in the management of early squamous neoplasia both for staging and (by piecemeal endoscopic resection in elderly unfit) for medium- to long-term disease clearance.